2020
DOI: 10.1021/acs.jpca.0c06615
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Photoabsorption Cross-Sections of Methanol for Terrestrial and Astrophysical Relevance

Abstract: We investigate the methanol absorption spectrum in the range 5.5− 10.8 eV to provide accurate and absolute cross-sections values. The main goal of this study is to provide a comprehensive analysis of methanol electronic-state spectroscopy by employing high-resolution vacuum ultraviolet (VUV) photoabsorption measurements together with state-of-the-art quantum chemical calculation methods. The VUV spectrum reveals several new features that are not previously reported in literature, for n > 3 in the transitions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(184 reference statements)
0
6
0
Order By: Relevance
“…The outer-valence MOs of methanol are (6a′) 2 , (7a′) 2 , and (2a″) 2 with σ CO , n O (2p x ∥ COH ), and n O (2p y ⊥ COH ) characters, respectively, where the lowest-lying electronic excitations have been assigned to mixed valence/Rydberg and mainly Rydberg character. 3 The TOF mass spectra of the different anions formed in potassium collisions with methanol were obtained from 19 to 275 eV in the lab frame (7.3−111.5 eV in the center-of-mass frame, CM). Figure 2 depicts a typical TOF mass spectrum recorded at 35 eV (E CM = 13.9 eV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer-valence MOs of methanol are (6a′) 2 , (7a′) 2 , and (2a″) 2 with σ CO , n O (2p x ∥ COH ), and n O (2p y ⊥ COH ) characters, respectively, where the lowest-lying electronic excitations have been assigned to mixed valence/Rydberg and mainly Rydberg character. 3 The TOF mass spectra of the different anions formed in potassium collisions with methanol were obtained from 19 to 275 eV in the lab frame (7.3−111.5 eV in the center-of-mass frame, CM). Figure 2 depicts a typical TOF mass spectrum recorded at 35 eV (E CM = 13.9 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations , have shown that the synthesis of complex molecules as prebiotic species in the ISM may be initiated by these secondary species. Among the different mechanisms occurring in such environments, one of the prevalent ones is molecular dissociation (MD), which can be initiated by UV photoabsorption and LEE capture, the latter either via electron attachment or electron transfer processes. Important aspects to consider are the type of prevalent local chemical and even physical conditions for such reactions.…”
Section: Introductionmentioning
confidence: 99%
“…An exception is found among our results for CH 3 OH, where EOM-CCSD embedded in CAM-B3LYP performs very well, whereas TD-CAM-B3LYP struggles to reproduce the full EOM-CCSD energy. This might be explained by the partial Rydberg character (3s) of this excited state [107] whose proper representation is difficult with TD-DFT. Rydberg excitations.…”
Section: Performance For Different Types Of Target Statesmentioning
confidence: 99%
“…photochemistry for O 2 and HO 2 following treatments inHu et al (2012) and CH 3 OH using experimental crosssections fromLange et al (2020) andBurton et al (1992).We couple planetary surface processes to our atmospheric models by adding influxes of species to the lowest layer of our atmospheres. These include: H 2 impact degassing, CO 2 outgassing from volcanoes, CH 4 outgassing from hydrothermal systems, H 2 O evaporation from the ocean, and chemical production (e.g.…”
mentioning
confidence: 99%